SISTEMA MULTIAGENTE EDUCATIVO (SME) PARA LA POBLACIÓN CON DISCAPACIDAD COGNITIVA - Becerra Correa, Nelson; Carmona, Edgar Altamirano (Revista Vínculos, 2013)
Here describes the development of a multi-agents system. Called System multiagents education -SME-. Whichteaches and reinforces the commonly used word for users with cognitive disabilities. This project is divided into four phases. This paper detail the development and implementation of the first phase, which we call “visual discrimination” Categories and Subject Descriptors H.4 [Information Systems Applications]: Miscellaneous; D.2.8 [Software Engineering]: Metrics—complexity measures, performance Measures